COMPARATIVE ANALYSIS OF DIPLOMATIC INTUITION AND PSYCHOLOGICAL PORTRAIT OF STATE LEADERS - Turkboev Javokhir Farhod ugli (Modern American Journals, 2025)
This article explores the dynamic interplay between diplomatic intuition and the psychological portrait of state leaders, emphasizing their roles in shaping international relations. By analyzing historical and contemporary figures such as Churchill, Hitler, Kennedy, Khrushchev, Putin, Merkel, and Trump, the paper highlights how intuition and psychological traits—such as resilience, empathy, narcissism, and cognitive flexibility—affect diplomatic outcomes. The study also considers the cultural and strategic implications of leader behavior in high-stakes global affairs. Understanding these dimensions offers valuable insight into the human factors influencing diplomacy, enabling better prediction of international decision-making and conflict resolution.
Keywords: Diplomatic intuition, psychological portrait, international relations, leadership behavior, political psychology, decision-making.